Evaluation of The Implementation of Utilization of Regional Property Through Borrowing and Use of Regional Property in the Siau Tagulandang Biaro Islands Regency - Shinta, I Dewa Ayu; Manossoh, Hendrik; Kapojos, Peter M. (Universitas Sam Ratulangi, 2022)
Regional property is one of the important elements in the framework of governance, development, empowerment and service to the community. This study aims to (1) find out the implementation of the utilization of regional property through borrowing and use in the Siau Tagulandang Biaro Islands Regency. This study uses a qualitative research with a descriptive approach which was carried out at the Regional Finance and Revenue Management Agency of the Siau Islands Tagulandang Biaro Regency in May 2021. The data collection method was carried out through interviews and documentation, the data analysis method was carried out by collecting and analyzing the data obtained and then pulling conclusion. The results of this study indicate that the procedures/stages in the implementation of lending and use are not in accordance with the Regional Regulation of the Siau Islands Tagulandang Biaro Regency Number 7 of 2019, because in its implementation there are several borrowing and use stages whose stages do not include the research stage, and there are still obstacles that occur in the asset sector related to the recording and data collection of regional property that has been/is temporarily borrowed and used.